MEASURING RELIGIOUS MODERATION AMONG STUDENTS - Amirudin Amirudin; Suyono Suyono; Soeprijanto Soeprijanto; Lu’luil Maknun (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
This article aims to describe the results of research on the analysis of factors that influence religious moderation and the influence of religiosity on religious moderation for students of UIN Syarif Hidayatullah Jakarta. The research was conducted at UIN Syarif Hidayatullah Jakarta in the odd semester of the 2022/2023 academic year. The approach used is quantitative. Data collection techniques through surveys and data analysis using simple linear regression analysis. The results of this study are 1) the correlation coefficient between graduated with religious moderation is 0.286 or 28.6%, 2) the correlation coefficient value between religious organization background and religious moderation is 0.124 or 12.4%. 3) the value of the correlation coefficient between gender and religious moderation is 0.095 or 9.5%, 4) the average value of religiosity is 4.4665 with a standard deviation of 0.23404. based on these factors, it was found that the religiosity factor had an effect on religious moderation, as evidenced by the results of the study the R2 value of 0.025 or 2.5%, . The conclusions are: 1) there is no relationship between educational background and student religious moderation, 2) there is no relationship between gender (gender) and religious moderation, 3) there is no relationship between the background of students' religious organizations and religious moderation, 4) there is the relationship between religiosity and religious moderation 5) there is an influence of the dimension of religiosity on religious moderation.